Genetic and imaging features of CADASIL patients with acute ischemic stroke - Jae Young Park; Jeong Yun Song; Jun Young Chang; Dong-Wha Kang; Sun U. Kwon; Chong Hyun Suh; Hyunjin Kim; Jae-Sung Lim; Satoshi Saito; Sang Hee Ha; Bum Joon Kim (Scientific Reports)
Abstract Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), which is caused by mutations in the NOTCH3 gene, is associated with early-onset strokes. However, the specific genetic and imaging characteristics associated with acute ischemic stroke (AIS) in patients with CADASIL remain unclear. We reviewed CADASIL patients with NOTCH3 mutations, dividing them into two groups based on the presence of clinically relevant AIS lesions on diffusion-weighted imaging, observed at any time, regardless of the timing of CADASIL diagnosis. Clinical, imaging, and genetic features were compared between these groups. Genetic variations were categorized by exon location: specifically, exon 3 including Arg75Pro, and exon 11 including Arg544Cys, were examined in detail. Factors associated with AIS in CADASIL patients were analyzed. A total of 141 patients were included, of whom 70 (49.6%) were diagnosed with AIS. While there were no significant differences in vascular risk factors between the two groups, patients with AIS had a higher prevalence and greater number of lacunes (p < 0.001) and exhibited more severe white matter changes (p = 0.007). CADASIL patients with AIS had a higher rate of exon 3 variant and a lower rate of exon 11 variant compared to those without AIS. Multivariable analysis revealed that exon 11 variants were associated with a reduced risk (aOR = 0.270, 95% CI 0.099–0.733; p = 0.010). CADASIL who experienced AIS had unique genetic and imaging characteristics when compared to those who did not experience AIS.